POTENCY OF QUININE AND QUINIDINE METABOLITE PRODUCTION OF ENDOPHYTE BACTERIA ISOLATED FROM CINCHONA PLANT (Cinchona ledgeriana Moens.) - AKHBAR ANUGRAH NIM: 20615005, FAUZI
The obstacles of quinine and quinidine production in Cinchona plant (Cinchona ledgeriana Moens.) with conventional method has initiated the research focusing on revealing the endophytes bacteria potential in biosynthesizing quinine and quinidine alkaloids. The aim of this research is to reveal the endophytes bacteria ability in producing quinine and quinidine outside their environment. Quinine and quinidine alkaloids extractions were conducted in Nutrient Broth medium with supplementary of 1% Cinchona leaves extract. The qualitative measurement with TLC and quantitative measurement with HPLC of quinine and quinidine extract revealed three isolate bacterium in which isolate A1 produced quinine 35,83 μg/mL quinine and 316,66 μg/mL quinidine, isolate B11 produced 28,94 μg/mL quinine and 461,28 μg/mL quinidine, and isolate B12 produced the highest of all with quinine concentration 58,79 μg/mL and quinidine 819,11 μg/mL. The 16S rRNA gene analysis of chosen bacteria showed that isolate A1 is related to Achromobacter xylosoxidans, isolate B11 is related to Bacillus mycoides, and isolate B12 is related to Bacillus subtilis. The growth ability of chosen isolates was evaluated by growing the bacterium on simple sugarcane juice media with variation of C/N ratio 3:1, 5:1, 7:1, 9:1, and 11:1 that was combined with variation of pH value of 5, 6, 7, 8, and 9, and was also combined with three different temperature at 23˚C, 30˚C, and 37˚C. Based on the highest biomass achieved at 18-hour, it was obtained respectively that isolate A.xylosoxidans is 1,09 X 108 cfu/mL of the C/N ratio 9:1, pH 7 at 30˚C, isolate B.mycoides is 1,26 X 108 cfu/mL of C/N ratio 11:1, pH 7 at 30˚C, and isolate B.subtilis is 1,76 X 108 cfu/mL of C/N ratio 9:1, pH 7 at 37˚C.